2006
DOI: 10.1159/000094996
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Risk Factors Increases the Incidence of Echolucent Carotid Plaque in Stroke Patients

Abstract: Background: The purpose of this study was to assess the influence of clusters of risk factors on the incidence of echolucent carotid plaque in stroke patients. Methods: A retrospective analysis of 413 stroke patients who had undergone carotid ultrasonography was performed. High-resolution B-mode ultrasonography was used to evaluate the characteristics of carotid plaque. We investigated the relationships between the incidence of echolucent carotid plaque and clustering of risk factors (hypertension, diabetes me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
1
4
1
Order By: Relevance
“…Our data are consistent with other work on the association of the CIMT [16] and the incidence of echolucent carotid plaque [17] with some cardiovascular risk factors. Recently, Granér et al [18] showed that CIMT seems a predictor of coronary arteriosclerosis in mid and distal parts of the coronary tree but not in proximal ones.…”
Section: Discussionsupporting
confidence: 93%
“…Our data are consistent with other work on the association of the CIMT [16] and the incidence of echolucent carotid plaque [17] with some cardiovascular risk factors. Recently, Granér et al [18] showed that CIMT seems a predictor of coronary arteriosclerosis in mid and distal parts of the coronary tree but not in proximal ones.…”
Section: Discussionsupporting
confidence: 93%
“…Echolucent plaques usually consist of a large lipidic or necrotic core with a thin fibrous cap, whereas echogenic plaques consist mostly of fibrous tissue and/or calcification 23–27. Echolucent plaques were found to be more at risk for stroke or cerebrovascular events than echogenic plaques and are thought to be more prone to rupture 2.…”
Section: Discussionmentioning
confidence: 99%
“…144 Echolucent plaque detected by high-resolution B-mode ultrasound correlates with clustering of conventional vascular risk factors and large-artery strokes compared with other stroke subtypes and compared with TIA. 145 Echolucency 144 and surface irregularity detected by MRI 146 can be correlated with symptomatic versus asymptomatic status. Recent reports with positron emission tomography and MRI correlate plaque inflammation with plaque stability.…”
Section: Vessel Imaging Extracranial Diseasementioning
confidence: 99%